Promoting Postpartum Exercise in Muslim Mothers - Sawan, Sarinee; Siriphan, Siriphan; Adulyarat, Manassavee; Suwannakan, Atcha; Samael, Lutfee (Princess of Naradhiwas University Journal, 2019)
Doing physical exercise after the postpartum period is important to adjust the mothers’ body from physical changes during pregnancy to a normal condition. Doing exercise not only increases physical strength, but also the mother’s mind after giving birth. In Narathiwat, Yala, and Pattani provinces, where the cultural context is mainly Muslim, postpartum mothers get less social support, and tend to limit their physical activity after giving birth. The Muslim cultural context might be the cause of this lack of physical exercise among postpartum mothers. So the nursing role is even more important for promoting postpartum exercise. This article aimed to present guidelines regarding postpartum exercise promotion for mothers in a Muslim context. This article includes 6 topics: 1) physical exercise in a Muslim context, 2) the benefits of postpartum exercise, 3) Islam’s precepts about exercise, 4) a postpartum exercise approach for mothers in a Muslim context, 5) how to overcomeproblems and barriers related to the Muslim context and focus on Health of the mothers, 6) nursing guidelines for promoting exercise among postpartum mothers in a Muslim context.